Perkembangan Implementasi Cash Waqf Linked Sukuk: Paradigma Baru Waqf Produktif di Indonesia - Hakim, Abd; Abdurrohman; Farid, Muhammad (Faculty of Islamic Economics and Business, Madura Islamic State University, 2024)
This research aims to evaluate CWLS practices that have been published by the government, then propose improvements that can be made for future development of the CWLS instrument. The methodology of this research is literature study research with a qualitative approach. This method involves analysis and synthesis of written sources that are relevant to answering research questions or understanding the problem being researched. Findings - The advantages of CWLS include that the risk is entirely borne by the Government, the returns offered are quite cooperative because they are free from tax, flexible in obtaining CWLS, and fully supported by various related agencies. Weaknesses in CWLS studied in this research include Human Resources, in this case, namely Nazhir, who is still relatively incompetent, especially in contemporary waqf science, and Sharia Financial Institutions, there are only 27 institutions that are partners in collecting CWLS. Opportunities that Indonesia can take advantage of in CWLS include the demographic bonus which will make the majority of Indonesia's population of productive age with the hope of participating in CWLS, Indonesia as the most generous country in the world, as well as a strong legal umbrella. The challenges that will be faced in CWLS are differences in opinion from Islamic Schools of Imams, traditional waqf is still strong in society, as well as moral hazards that may occur within social institutions.